(untitled) (Baghdad Science Journal, 2011)
In this work dithine complexes prepared from dithiol benzil ligand and central ion to the Ni,Pd,Pt, element the ligand and complexes have been investigated using FTIR spectrophotometer and uv-vis-NIR spectral reigns show higher intensity represents the ?-?* transition in the chromopher cycle .These absorption which appear in visible and near IR spectral regions ,According to the complexes of one group ,the spectral shifting due to the change of central ion has been found to be related to atomic number of central ion .This shifting is increased while decreasing the central ion atom number These complexes have been implemented in Nd+2:YAG cavity because each posses resonant absorption band near Nd+2:YAG, Nd+2:Glass emitting at (1060nm). pulse duration measured to complexes dissolved in dioxin(2*10-3M) is very short compared with free running pulse duration ,therefore the complexes work as Q-switch to the NIR lasers.